Subconscious Memory Narrative In The Exploration Of Iconic Puppet Of I Ketut Teja Astawa’s Painting - I Wayan Seriyoga Parta; I Wayan Suardana (Institut Seni Indonesia Denpasar, 2020)
The process of creation in creating works of art is stimulated by various factors, one of which is the personal experience of the artist who is so imprinted that makes it an inspiration and motivation in the work. In the context of the creation of experiential works of art, it then undergoes a process of internalization and interpretation in an artist, which is then reconstructed back into the medium of art. The reconstruction is related to the reimagining process, which at the level of implementation can vary by artist. Similarly, the work process of Teja Astawa, a young artists who grew up in the coastal environment of Sanur, Bali. Teja’s works highlight his childhood experiences when playing with frangipani leaves and jackfruit leaves which then made into various forms of puppets. That experience made an impression and room in Teja’s artistic life as an adult, especially in the media of painting. Teja also re-knits the series of experiences by bringing back the puppet figures in his work. To begin the reconstruction process, Teja conducted a field study by observing various forms of puppets with their respective symbolic characters.